Anomia y extinción de dominio: una mirada fundamentadora a la figura constitucional - Vargas Tamayo, Camilo Alfonso (Derecho penal y criminología, 2024)
The forfeiture has a poor dogmatic evolution in comparison with other criminal law institutions. Most contributions identified the grounds of this concept in the inside of the legal system. They frequently locate the forfeiture foundations in the Constitution, the statues or as a manifestation of the criminal law of the enemy. The purpose of this article is to give a different basis to this legal concept, from the outside of the legal system. It uses the anomy theory developed by Robert King Merton to state that forfeiture is in his essence a router of anomy, as it gives mayor emphasis to the procedure than to its social goals.